Compositional characteristics of black-carbon and nanoparticles in air-conditioner dust from an inhabitable industrial metropolis. (10th April 2018) - Ali, Muhammad Ubaid; Liu, Guijian; Yousaf, Balal; Abbas, Qumber; Ullah, Habib; Munir, Mehr Ahmad Mujtaba; Zhang, Hong
Abstract: Atmospheric dust, especially air-conditioner dust in urban-industrial environments, can act as a significant sink for both black carbon and nanoparticles posing allied health risks to the air conditioner repairman as well as to local inhabitants. However, the chemical composition of black carbon/nanoparticles in air-conditioner dust and their association with potentially toxic elements remain uncertain. The present study investigate the black carbon and nanoparticles compositions of air-conditioner dust and their associated potentially toxic elements, as an indicator of indoor air-pollution. The black carbon and nanoparticles in air-conditioner dust, were comprehensively characterized using array-based techniques including Inductively Coupled Plasma-Mass Spectrometry, particle size distribution, Scanning Electron Microscopy, Transmission electron microscopy along with Energy-dispersive X-ray spectroscopy and selected area-(electron) diffraction, from metropolitan area of Hefei, China. Geo-accumulation index values of air-conditioner dust reveal Lead, Tin, Arsenic and Cadmium are under Geo-accumulation Classes V-VI level of contamination. The majority of the particles were found to be in the ultrafine nanoparticles range (<100 nm). A strong correlation was found between black carbon and total potential toxic elements content (R 2  = 0.79). The metallic nanoparticles (Iron, Copper and Lead) and black carbon were identified using Scanning Electron Microscopy/Transmission electron microscopy along with Energy-dispersive X-ray spectroscopy/selected area (electron) diffraction mode. Using array-based techniques seems to be a useful tool to study the black carbon and nanoparticles in air-conditioner dust. It is the first demonstration presenting evidence for the concept of air-conditioner dust as a sink for black carbon/nanoparticles bound potentially toxic elements in the urban-industrial environments, as an ultimate source of environmental pollutants. Highlights: Composition of BC/NPs in AC dust and their associated PTEs were investigated. This study presents evidence for the concept of AC dust as a sink for BC/NPs-PTEs. The dominant NPs identified using SEM/TEM/EDS/SAED analyses were Fe, Cu and Pb. Black carbon contents in AC dust were in the range of 36.19–240.64 mg g −1 . The ƩPTEs contents were positively correlated (R 2  = 0.79) with BC.